Depressive symptoms, pain, and sexual dysfunction over the first year following vaginal or cesarean delivery: A prospective longitudinal study. Issue 9 (September 2015) - Chang, Shiow-Ru; Chen, Kuang-Ho; Ho, Hong-Nerng; Lai, Yeur-Hur; Lin, Ming-I; Lee, Chien-Nan; Lin, Wei-An
Abstract Background Childbirth has a significant impact on maternal health, and the high rate of cesarean delivery is a global health concern. Few studies have used validated measures to explore depression, pain, and sexual dysfunction following vaginal or cesarean delivery over a prolonged time period. Objective We examined the associations between vaginal and cesarean delivery and depressive symptoms, pain, and sexual function during the 1-year postpartum period. Design A prospective, five-time-point longitudinal study. Setting Maternity unit at a medical center. Participants A total of 351 of 736 women completed a questionnaire that described demographic characteristics, depressive symptoms, and pain levels at 3–5 days postpartum, and updated personal data, depressive symptoms, pain levels, and sexual function at 4–6 weeks and at 3, 6, and 12 months after delivery. Methods Differences between the vaginal and cesarean groups in depressive symptoms, pain, and sexual function and trends of changes in these factors over the first postpartum year were examined. Results Compared with the vaginal birth group, the cesarean birth group had a significantly higher prevalence of depressive symptoms at 3 months (p = 0.03); higher scores for non-localized pain at 3–5 days (p < 0.001), 4–6 weeks (p = 0.03), and 3 months (p = 0.046); higher scores for abdominal pain at 3–5 days (p < 0.001), 4–6 weeks (p < 0.001), and 6 months (p = 0.01); lower perineal pain scores at 3–5 days (p <0.001); and higher sexual desire scores (p = 0.04) but lower sexual satisfaction scores (p = 0.02) at 4–6 weeks. Differences between the vaginal and cesarean groups were significant (p = 0.01, p = 0.049, respectively) in terms of the decrease in non-localized pain from 3–5 days to 4–6 weeks postpartum and the increase in sexual desire from 4–6 weeks to 3 months postpartum. Conclusions Cesarean delivery was associated with an increased prevalence of depressive symptoms at 3 months and higher pain levels that persisted at 6 months postpartum in Taiwan. We found no difference in sexual function between vaginal and cesarean delivery after 6 weeks postpartum, and no differences in the trends related to depressive symptoms or in sexual functioning (except for desire) within 1 year postpartum.